Import-by-Query: Ontology Reasoning under Access Limitations. - Grau, B; Motik, B; Kazakov, Y (2009)
To enable ontology reuse, the Web Ontology Language (OWL) allows an ontology Kv to import an ontology Kh. To reason with such a Kv, a reasoner needs physical access to the axioms of K h. For copyright and/or privacy reasons, however, the authors of Kh might not want to publish the axioms of Kh; instead, they might prefer to provide an oracle that can answer a (limited) set of queries over Kh, thus allowing Kv to import Kh "by query." In this paper, we study import-by-query algorithms, which can answer questions about Kv ∪ Kh by accessing only Kv and the oracle. We show that no such algorithm exists in general, and present restrictions under which importing by query becomes feasible.